Symbiotic nitrogen fixation in legumes as a genetic and selection trait - K. K. Sidorova; M. N. Glyanenko; T. M. Mishchenko; E. Yu. Vlasova; V. K. Shumny (Вавиловский журнал генетики и селекции)
The results of long-term studies on legume symbiogenetics and breeding are summarized by the example of pea Pisum sativum L. A collection of symbiotic mutants was developed by chemical and radiational mutagenesis of pea varieties and genetically characterized. Various sym genes were recognized. From the large set, supernodulating (proved to be recessive) and dominant hypernodulating types of symbiotic mutants were chosen for breeding programs. Varieties differed dramatically in hypernodulation degree. Aiming at nitrogen fixation intensification, accessions bearing recessive genes for supernodulation (nod4) and dominant genes for hypernodulation (Nod5) were selected. The recurrent method of symbiotic mutants utilization in pea breeding for nitrogen fixation intensification was developed. The best results were obtained by combining two sym genes in one pea genotype: the dominant hypernodulation gene Nod5 and the recessive supernodulation gene nod4. A set of recurrent lines tagged with both these genes was raised to use in breeding programs as donors of intense nitrogen fixation combined with good performance. In addition, they are good preceding crops. After their harvesting, soil accumulates large amounts of nitrogen-rich root and bacterial biomass. The nitrogen is preserved for years, whereas mineral nitrogen is rapidly washed out with precipitation. Endemic pea accessions originated from various regions can be successful starting material in breeding for nitrogen fixation intensification, accessions from Egypt and Syria having provided best results. Nodulation and nitrogen fixation intensities were assessed in seven cultivars derived from three promising pea lines raised at the Siberian Research Institute of Plant Breeding and Selection.